The influence of intraoperative sedation on memory consolidation: a single-blind randomized controlled trial - V. O. Churakov; A. Yu. Zaitsev; G. D. Vzorin; A. M. Bukinich; K. V. Dubrovin; K. V. Anokhin; V. V. Nourkova (Вестник анестезиологии и реаниматологии)
The objective was to evaluate the effect of propofol and dexmedetomidine sedation on the short-term memory and long-term memory consolidation.Materials and methods. 80 patients with small orthopaedic interventions under subarachnoid anesthesia were included in the randomized controlled trial. Three groups were formed depending on the drug used: group P – propofol, group D – dexmedetomidine, group 0 – control. Emotionally neutral sets of words were tapped three times to evaluate the effect of sedation on long-term memory consolidation: stage1/set 1 – immediately before sedation (RASS 0, BIS 95–100), stage 2/set 2 – 5–10 minutes after the start of sedation (RASS «–1» – «–2», BIS 70–90), stage 3/set 3 – 10 minutes after sedation was terminated and consciousness was recovered (RASS 0, BIS 90–100). In addition, the impact of sedation on the ability to hold the received information in short-term memory was conducted 5 minutes after the presentation of the words at stage 2. Reproduction and recognition testing of all words was conducted the next day after operation to evaluate the effect of medical sedation on long-term memory consolidation.Results. Propofol and dexmedetomidine provided an inhibitory effect on the ability to hold information in short-term memory compared to control group (р < 0.001 и р < 0.001, respectively). Propofol had the most effect on short-term memory and the level of its amnesic effect was associated with the cognitive function of patients (p = 0.013, R² = 0.23, β = 0.472). The HADS points were as negative predictor of the reproduction of the word set 1 in control group (p = 0.05, R² = 0.136, β = –0.368) and recognition of the word set 3 in propofol group (р = 0.029, R² = 0.176, β = –0.420). Within 24 hours after operation, reproduction and recognition of word sets 2 depended on the degree of short-term memory impairment during sedation (F(1.65) = 19.317, p < 0.001, ηp2 = 0.229 и F(1.65) = 21.638, p < 0.0031, ηp2 = 0.250, respectively). Short-term memory test acted as a positive predictor of the reproduction of word set 3 in control group (p = 0.05, R² = 0.141, β = 0.376).Conclusion. Propofol and dexmedetomidine impair the ability to retain information in short-term and, consequently, long-term memory, and propofol has a more pronounced amnesic effect, which depends on the cognitive functions of patients. The sensitivity to the amnesic effect of the drugs depends on the individual characteristics of the patients.